The Violation of Nurses' expectations of Patients at Sebelas Maret University Hospital, Case Study of Oncology Inpatients: A Qualitative Research - Lestari, Eni; Rahmanto, Andre Noevi (Jurnal Berita Ilmu Keperawatan, 2025)
Patient service satisfaction is an important factor for hospitals in maintaining their reputation and being trusted by the community. The violation of expectations between nurses and patients is an obstacle to service satisfaction and affects the hospital's reputation in the community. This study aims to find out the form of violation of nurses' expectations of patients and how the public relations strategy in carrying out its role manages the violation of expectations. Descriptive qualitative research case study. Data collection techniques with interviews, using the purpose sampling method. Data analysis was carried out using the data matching pattern technique, namely the hypothesis between the research results and the theory used, and then conclusions were drawn. Data validation with triangulation of sources and data. This study succeeded in describing the form of violation of nurses' expectations of patients by drawing conclusions from field data with the theory of assumptions of violation of expectations from Judee Burgoon. Nurse communication when providing health services raises violations of patient expectations by being slow to respond to complaints, unfriendly and impolite, and public relations strategies manage violations of expectations according to Dozier and Broom's theory, namely as expert advisors, communication facilitators, and problem solvers. Forms of violations of nurses' expectations of patients: Nurses are less alert to address patient complaints. Nurses use body language that is less polite in communication. Nurses lack skills and knowledge in care services to patients. The public relations strategy in carrying out the role to overcome the form of violation of expectations is to provide input to management as a bridge between the two parties and carry out ongoing training to improve nurses' communication skills. The results of the study will minimize the occurrence of violations of expectations and increase service satisfaction, which affects public trust.